Antisynthetase syndrome: a case report and review of the literature. - Fiialkovska , Olesia; Karasevska , Tetiana; Ivashkivskyi , Oleksiy; Potomka , Ruslana; Novytska , Hanna; Dzhus , Marta (The Ukrainian Scientific Medical Youth Journal, 2023)
antisynthetase syndrome is a rare autoimmune disease characterized by interstitial lung disease, non-erosive arthritis, myositis, Raynaud’s disease, and/or "mechanic hand" when autoantibodies directed against aminoacyl-tRNA synthetases are detected. Antisynthetase syndrome belongs to the group of idiopathic inflammatory myopathies and is the so-called overlap myositis. The article provides the latest literature data on the diagnostic value of myositis-specific autoantibodies based on a literature review for the period from 2013 to 2023 using the scientometric databases MEDLINE/ PubMed, Wiley Online Library, and Scopus. Data from the literature show that certain myositis-specific autoantibodies, namely anti-PL-7 and anti-PL-12, can affect the risk of developing interstitial lung disease, and determine the course and prognosis of the disease. The presence of interstitial lung disease in patients with myositis correlates with increased morbidity and mortality. The article describes a clinical case of the debut of the antisynthetase syndrome from interstitial lung disease, which was falsely diagnosed as a coronavirus disease. The patient’s condition improved only because of using glucocorticoids, which the patient stopped taking over time, which led to the worsening of pulmonary symptoms, the appearance of new clinical signs of damage to the joints and skin, progressive decrease in muscle function, and dysphagia. After an examination in the rheumatology department, based on the presence of interstitial lung disease in the patient - fibrotic alveolitis, which was confirmed by computer tomography, myositis, arthritis, characteristic skin changes, the presence of antinuclear antibodies, anti-SS-A/Ro52, specific antisynthetase antibodies (Jo-1, Pl-7, Pl-12), the diagnosis of the antisynthetase syndrome was established. A detailed laboratory and instrumental examination made it possible to rule out a paraneoplastic process at the time of examination. The prescribed treatment included pulse therapy with methylprednisolone and cyclophosphamide, which led to improvement in the patient’s condition. The work carried out emphasizes the need for interdisciplinary interaction of pulmonologists, rheumatologists, and infectious disease specialists at the stage of verification of the final diagnosis and the therapy appointment. Achieving clinical and laboratory remission of the disease requires long-term monitoring by a rheumatologist.